For the function $f(x)=x+\frac{1}{x}, x \in[1,3]$, the value of $c$ for the Lagrange's mean value theorem is
(a) 1
(b) $\sqrt{3}$
(c) 2
(d) none of these
(b) $\sqrt{3}$
We have
$f(x)=x+\frac{1}{x}=\frac{x^{2}+1}{x}$
Clearly, $f(x)$ is continuous on $[1,3]$ and derivable on $(1,3)$.
Thus, both the conditions of Lagrange's theorem are satisfied.
Consequently, there exists $c \in(1,3)$ such that
$f^{\prime}(c)=\frac{f(3)-f(1)}{3-1}=\frac{f(3)-f(1)}{2}$
Now, $f(x)=\frac{x^{2}+1}{x}$
$f^{\prime}(x)=\frac{x^{2}-1}{x^{2}}, f(1)=2, f(3)=\frac{10}{3}$
$\therefore f^{\prime}(x)=\frac{f(3)-f(1)}{2}$
$\Rightarrow \frac{x^{2}-1}{x^{2}}=\frac{4}{6}$
$\Rightarrow \frac{x^{2}-1}{x^{2}}=\frac{2}{3}$
$\Rightarrow 3 x^{2}-3=2 x^{2}$
$\Rightarrow x=\pm \sqrt{3}$
Thus, $c=\sqrt{3} \in(1,3)$ such that $f^{\prime}(c)=\frac{f(3)-f(1)}{3-1}$